Master Studies in Education Sciences in Today’s Society: The Graduates’ Attitude - Pilkienė, Simona; Sajienė, Laima (Pedagogika, 2013)
European Higher Education Area, the market economy and the labor market, the change of concept of study quality and its relation to the labor market, the changes of society and concept of vocational education influence the university and labor market interactions. The research problem – the curriculum of master studies in education sciences does not reflect actual interaction between mass higher education and the labor market needs. The article seeks to identify the approach of graduates to mission of master studies in education science in today’s society, the importance of the development of their personality and professional career. The results have shown that the mass phenomenon of the graduates of higher education in education sciences is perceived positively: the aim of mass higher education is to develop a holistic education of person, not specifically defied professional activities. Graduates evaluating the mission of master studies in education sciences, in the context of needs of labor market, distinguish the independent, critical-thinking, innovation developing education of personality. Such a choice confirms the importance of master studies in education sciences to analysis of the results of personal life. Master of Education sciences enrolls students with the motivation to continue their studies in education, some of them are already working in the education system. Master studies of Education sciences is focused on the research works, quality of education assessment and development of managerial competencies. Meanwhile, little attention has been paid to educational policy analysis, career guidance, expertise, consultancy, project work skills development. While the pedagogical competence development in education graduate studies has been given little attention, but graduates in this professional activities feel strong and think that researchers with Master degree of education science also need a teacher qualification. Most of the graduates had not the opportunity to practice, but notes that they were missing. In postgraduate student opinion, practice should aim to adapt existing theoretical knowledge and abilities in specific work situations and gain the skills and experience needed for their future careers. Most of the surveyed graduates work in the field of education. However, the unanimous consensus, whether professional activities require the master of education sciences degree, is absent. Graduates with Master of Education Sciences degree have occupied various positions in professional activities: from the highest executive positions to specialist in administrative, didactic, project and research area.